Method of increasing the QR code capacity – Hexa QR Code - Janowski, Daniel (Journal of Computer Sciences Institute, 2018)
The article presents the author’s method of increasing the QR code capacity through using their property of being readable from any perspective. The symbol encoding and decoding process and test results are presented. The article also includes a literature review in the field of method of increasing the QR code capacity.